Pemanfaatan Platform Merdeka Mengajar dalam Pembelajaran Bahasa Indonesia oleh Guru Pelaksana Kurikulum Merdeka di SMP Kabupaten Gowa - Nurlaela, Nurlaela; Salam, Salam; Sultan, Sultan (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2025)
This research aims to (1) describe the use of the Merdeka Mengajar Platform by teachers implementing the Merdeka Curriculum in Indonesian Language learning in junior high schools throughout Gowa Regency (2) describe the challenges faced by teachers implementing the Merdeka Curriculum in utilizing the Merdeka Mengajar Platform in Indonesian Language learning in junior high schools throughout Gowa Regency. This type of research is qualitative research using descriptive methods. Data collection techniques were carried out through observation, documentation, and interviews. The results of the study revealed that the Merdeka Mengajar Platform provides a number of benefits felt by teachers in the learning process. In terms of utilization, this Platform is used as a tool for learning, a source of reference, a training facility, and a medium for work. Although the Platform provides significant benefits, there are several challenges faced by teachers. These challenges include technical challenges such as unstable internet access and limited technological infrastructure as major obstacles, which affect the effectiveness of the overall use of the Platform. Skills aspects, such as the lack of digital literacy and technological skills among some teachers cause difficulties in utilizing all the Platform's features to the fullest. Resource aspects, including limited time, funds for hardware, and inadequate institutional support are also barriers to effective utilization of the Platform.